Grande sonate pour piano dédiée à Mr. le Comte F. de Brunswik par L. van Beethoven. Oeuvre 57 - Beethoven, Ludwig van, 1770-1827 (composer):::Creator:::::::::::: (France; S. Richault, 2023)
Early edition of the Piano Sonata no. 23 in F minor, op. 57, published in Paris by S. Richault and reissued as part of a collection.